AMFR and DCTN2 genes cause transplantation resistance of adipose-derived mesenchymal stem cells in type 1 diabetes mellitus - Horiguchi, Michiko; Tsurudome, Yuya; Ushijima, Kentaro (Frontiers in Pharmacology, 2022)
Type 1 diabetes mellitus (T1DM) is characterized by pancreatic beta cell destruction by autoantibodies and other factors, resulting in insulin secretion deficiency. Therefore, beta cell regeneration would be necessary to cure the disease. Nevertheless, the impact of type 1 diabetes on the stemness and transplantation efficiency of stem cells has not been previously described. In this study, we used next-generation sequencing to identify genes differentially expressed in T1DM adipose-derived stem cells (T1DM ADSCs) that originate from patients with type 1 diabetes. Furthermore, we evaluated their effects on transplantation efficiency following xenotransplantation into immunodeficient mice. In the T1DM ADSCs transplant group, the volume and weight of the graft were significantly reduced and the transplant efficiency was reduced. Next-generation sequencing and quantitative PCR results showed that T1DM ADSCs had significantly increased expression of AMFR and DCTN2. AMFR and DCTN2 gene knockdown in T1DM ADSC significantly restored cell proliferation and stem cell marker expression. Therefore, transplantation of T1DM ADSCs, in which AMFR and DCTN2 were knocked down, into immunodeficient mice improved transplant efficiency. This study revealed that AMFR and DCTN2 can reduce transplantation efficiency of T1DM ADSCs. Focusing on AMFR and DCTN2 is expected to increase the efficiency of stem cell transplantation therapy for diabetic patients.